The impact of brain-systemic oxygenation coupling in sleep-disordered breathing on cognitive function in elderly - Makoto Kawai; S. M. Hadi Hosseini; Casey Buck; Rosy Karna; Kai Ayinde Parker-Fong; Pahnwat Tonya Taweesedt (Scientific Reports)
Abstract Background: Intermittent hypoxia, a consequence of sleep-disordered breathing (SDB), may contribute to an increased risk of cognitive decline. However, the association between SDB and cognition remains highly variable. Methods: Fifty-two community-dwelling healthy older adults (28 women) were recruited. All participants underwent neuropsychiatric evaluations, simultaneous ambulatory polysomnography (PSG), and near-infrared spectroscopy (NIRS) recordings. We quantified the average coherence between oxy-Hb and SpO2 signals during SDB events to determine whether it could predict cognitive outcomes in healthy older adults, where higher coherence indicates reduced protection against systemic hypoxia. Results: The mean (SD) coherence of oxy-Hb and SpO2 was 0.16 (0.07). Linear regression analysis showed a significant association between mean coherence and worse Stroop Color Word Test scores (t=-0.304, p = .004). In contrast, oxy-Hb reduction alone and conventional SDB parameters did not show a significant association with cognition. Conclusion: This is the first report to demonstrate an association between a novel parameter of brain-systemic oxygenation coherence in SDB and cognition in older adults. A higher coherence rate of cortical oxy-Hb and systemic SpO2 during SDB may reflect a loss of compensatory mechanisms against systemic hypoxia and could help stratify older adults with a higher risk for cognitive decline.